Portugal nautical stations: Strategic alliances for sport tourism and environmental sustainability - Pereira, Elsa; Martins, Rute; Marques, João Filipe; Flores, Adão; Aghdash, Vahid; Mascarenhas, Margarida (Frontiers in Sports and Active Living, 2022)
Nautical tourism is a tourist product with great development in the European space and a lot of potential to promote and develop tourist destinations. Considering the dynamics of nautical tourism management and the importance of meeting the specificities of this market niche, the objective of this study is to analyse the strategic alliances for the development of the offer of nautical tourism products, namely their strategic goals and sustainable environmental practices adopted by the actors which integrated the strategic alliances in order to certificate a plethora of nautical stations in Portugal. Between September-December 2021, the application forms from 17 Portuguese nautical stations were collected. Content analysis using Nvivo software was the technique used for data analysis. The results show a multiplicity of strategic objectives associated with the strategic alliance established between the nautical stations. The strategic vision of nautical stations for the development of strategic alliances is based, firstly, on the objective of structuring the tourism offer, followed by increasing governance and promoting and marketing nautical tourism using the image of the destination. Based on these results, it is possible to infer the importance of nautical stations in destination competitiveness and the role of strategic alliances in facilitating penetration in the nautical tourism market. The managers of nautical stations should consider the use of strategic alliances to make a cooperative marketing in order to improve the experience to the clients. Regarding environmental sustainability practices, the results show the prominence of environmental education actions in contrast to the reduced number of nautical stations that develop actions for the adoption of sustainable transport. This study contributes to a better understanding of nautical tourism and Portuguese nautical stations, a project of strategic investment in sport and tourism, inferring on the objectives underlying the formation of strategic alliances and on the adopted environmental sustainability practices. The conclusions of this study point to the need for future scientific research on the actual operationalization of the objectives underlying the formation of strategic alliances, as well as the environmental practices developed by nautical stations.